Atmospheric pollution by automotive vehicles in São Paulo Metropolitan Area: causes and impacts - Testa, Joara Fernanda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This essay has a goal to understand the factor that have been favoring the pollutant emissions by automotive vehicles in SPMA (São Paulo Metropolitan Area) and to highlight the impacts made by them to the human health and to the environment. The polices to ease the credit joined with the oil taxes reductions has been promoting an increase of the number of private vehicles in Brazil, including in the SPMA, where the vehicle fleet is over six million units. With the private vehicles increase, greater are the pollutant gases released in the atmosphere creating even more impacts to the society and to the environment. In the last few years some actions were taken to decrease to pollutant levels in the atmospheric air in that area, however the increased number of private automotive vehicles has been canceled the initials and positive outcomes obtained by those measures.